Total esterase activity in human saliva: Validation of an automated assay, characterization and behaviour after physical stress. (18th May 2016) - Tecles, Fernando; Tvarijonaviciute, Asta; De Torre, Carlos; Carrillo, José M.; Rubio, Mónica; García, Montserrat; Cugat, Ramón; Cerón, José J.
Abstract: Although saliva has esterase activity, this activity has not been characterized or studied in individuals subjected to physical stress. The aim of this report was to develop and validate an automated spectrophotometric assay for total esterase activity measurement in human saliva, as well as to study the contribution of different enzymes on this activity and its behaviour under physical stress in healthy subjects. The assay used 4-nitrophenyl acetate as substrate and was precise, accurate and provided low limits of detection and quantification. Inhibition with diisopropylfluorophosphate showed that cholinesterase, carboxylesterase and cholesterol esterase contributions not represented more than 20% of total esterase. Addition of standards of lipase and albumin to saliva samples showed that both proteins significantly contributed to esterase activity only when equal or higher than 11.6 IU/L and 250 μg/mL, respectively. Western blot analyses showed absence of paraoxonase-1 and high amount of carbonic anhydrase-VI. The high affinity of purified carbonic anhydrase-VI for the substrate supported a major contribution of this enzyme. Total esterase activity and alpha-amylase was measured in saliva samples from 12 healthy male students before and after participation in an indoor football match. The activity significantly increased after match and positively correlated with salivary alpha-amylase. This method could be used as a biomarker of physical stress in humans, with carbonic anhydrase-VI being the esterase that contributed more to the activity of the assay.